Analysis of the energy performance of an Opaque Ventilated Façade under winter and summer weather conditions. (15th July 2020) - Gagliano, A.; Aneli, S.
Highlights: Computational fluid dynamic analysis of an Opaque Ventilated Façade. Summer and winter analysis. Wind and exposure façade affect the performances of OVF. Daily energy fluxes and energy-saving achievable by the OVF. Abstract: Nowadays, there is continuing worrying about energy efficiency and the reduction of GHG emissions in the building sector. It has been claimed that ventilated building envelopes help to reduce energy use in buildings and improve occupant comfort. This study proposes a comprehensive comparison of the thermal behaviour between an Opaque Ventilated Façade (OVF) and a conventional unventilated Façade (UF) considering two reference days for the winter and summer period. The analysis is developed investigating different façade orientations and two states of windiness, which are a state of calm wind and a state with wind velocity higher than zero (i.e. 5.0 m/s at 10 m of height) are taken into account. These analyses were developed utilizing fluid-dynamic calculation under dynamic conditions. Thus for the two façades were calculated: (I) the hourly surface temperatures of the most external, (II) the temperature profiles for all the facade's layers; (III) the airflow profiles inside the cavity and near the façade; (IV) the hourly thermal fluxes that cross the façade. Finally, the daily energy fluxes and the energy-saving, achievable through the adoption of the OVF, is calculated for the different façade exposures and the conditions of windiness. The outcomes of this study highlight that the OVF guarantees an energy-saving ranging from 20 to 55%, with the highest rate during the summer day for the façade facing East/West.